Accumulative effect of partial discharges at impulse voltage wave tail. Issue 5 (1st July 2020) - Florkowski, Marek
Abstract : This study describes a technique for evaluating partial discharges at fast impulse voltages. Fast transient voltages are increasingly present in power equipment and industrial environments due to the ubiquitous application of power electronics switching devices. Special attention should be paid to the dangers caused by the accumulative effect of repetitive impulse voltages on electrical insulation. This study describes a method of analysing partial discharges occurring during impulse voltage stimuli. A repetitive train of pulses is applied to a dielectric specimen and the accumulated PD pattern is obtained. This study focuses on the reverse discharges which occur during the tail part of the impulse voltage waveform acquired in time‐resolved mode. Investigations of the partial discharges in the wave tail can potentially lead to greater degradation of the insulation due to the formation of longer, repetitive sequence occurring along the decaying impulse voltage tail. Experiments were performed which investigated the influence of rise time, fall time and peak voltage on discharge pattern reshaping, intensity and time to inception on the tail. In the future, such an approach might be further developed for diagnostic applications and for extended factory tests.